PEMAHAMAN KONSEP PENILAIAN AUTENTIK KURIKULUM 2013 PADA GURU SD NEGERI 111 PEKANBARU - Hidayati, Rahmatul; Noviana, Eddy; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this research to describe teacher’s understanding of the concept of authentic assessment curriculum of 2013 in SD Negeri 111 Pekanbaru. The research was conducted from November 2015 to April 2016. this research is descriptive quantitative approach. Subjects in this research were 26 teachers in SD Negeri 111 Pekanbaru. The data used in this study of authentic assessment comprehension tests and interviews. The results of the research data showed understanding of the concept of authentic assessment of curriculum in 2013 in the sub-indicators sense of authentic assessment obtained an average of 23.08 with less category, the sub indicators characteristics and authentic assessment measures obtained an average of 26.93 with less category, the sub indicators forms, processes and authentic assessment tool gained an average of 45.38 with less category, the sub indicators charging gradebook gained an average of 64.42 with enough categories, the sub indicators of the implementation of assessment at the end of the learning process, both oral and writings gained an average of 78.85 with both categories, the sub-indicators of the availability of the assessment results document mastery of knowledge gained an average of 73.08 with both categories. While the sub-indicators used assessment instruments in accordance with the rules of authentic assessment obtained an average of 41.03 with less category. In sub indicator momentum assessment gained an average of 75.00 with both categories, the sub-indicators of the availability of the products of learning outcomes gained an average of 59.62 with enough categories, the sub-indicators of the availability of a complete set of learning outcomes of students with the teacher in the comments and ratings the portfolio gained an average of 50.00 with enough category. While the sub-indicators the creation of an atmosphere or aura of a conducive learning gained an average of 73.08 with both categories, and sub indicators creation of kilter atmosphere for learning obtained an average of 80.77 with both categories. Overall results of the research in SD Negeri 111 Pekanbaru shows that the understanding of the concept of authentic assessment curriculum 2013 of teachers is enough with an average value of 57.60.Key Words : Teacher’s Understanding, Authenctic Assesment